2017
DOI: 10.1002/ajmg.a.38515
|View full text |Cite
|
Sign up to set email alerts
|

How chromosomal deletions can unmask recessive mutations? Deletions in 10q11.2 associated with CHAT or SLC18A3 mutations lead to congenital myasthenic syndrome

Abstract: A congenital myasthenia was suspected in two unrelated children with very similar phenotypes including several episodes of severe dyspnea. Both children had a 10q11.2 deletion revealed by Single Nucleotide Polymorphisms array or by Next Generation Sequencing analysis. The deletion was inherited from the healthy mother in the first case. These deletions unmasked a recessive mutation at the same locus in both cases, but in two different genes: CHAT and SLC18A3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…16 Stankiewicz et al identified 24 patients with common clinical feature development retardation and intellectual disability with 10q11.21-q11.23 deletion. 9 It has been shown that 10q11.21q11.23 region is a recurrent deletion site, although the fracture regions vary. 8 Other cases of a 10q11.2 deletion showed a development delay patient, 17 Additionally, Langley et al reported a patient with hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Stankiewicz et al identified 24 patients with common clinical feature development retardation and intellectual disability with 10q11.21-q11.23 deletion. 9 It has been shown that 10q11.21q11.23 region is a recurrent deletion site, although the fracture regions vary. 8 Other cases of a 10q11.2 deletion showed a development delay patient, 17 Additionally, Langley et al reported a patient with hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The only clinical feature common to a majority of patients were intellectual disability and developmental delay 9. To date, over 30 cases with variable deletions of 10q11.22-q11.23 have been reported in literature.Chen et al reported a 22-week fetus with a 10q11.21q11.23 (45,946,150--50,945,014) Â 1 deletion.…”
mentioning
confidence: 99%
“…Our group previously developed a mouse model with reduced expression of VAChT (VAChT KD HOM ) and found motor, 10,11 cardiac, 28 and synaptic 4,[8][9][10]12 alterations that resemble some of the features later discovered in CMS patients with mutations in VAChT. 6,7 Interestingly, adult animals already exhibit cognitive and behavioral impairment, with a 40% to 50% decrease in expression level of VAChT, 10 suggesting that central cholinergic synapses are even more sensitive to decreased VAChT activity than peripheral synapses, in which symptoms appear only after a 70% decrease in VAChT expression. 10 However, the possible effects of a long-term reduced ACh release at the neuromuscular junction have not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene were recently identified in patients with different types of CMS (OMIN No. 617239) . Complete loss of function of VAChT disrupts the basis of cholinergic neurotransmission, leading to severe hypotonia and respiratory failure in humans .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation